BUILDING SUCCESSFUL DELEGATES: KEYS TO IMPROVING TEAM PRODUCTIVITY - Ayuzza Bintang Kesuma; Amelia Putri Tambunan, Fayyi Fawaz Tamir, Josua Pebriano Lumban Gaol, Sultan Al Fatah (International Journal of Teaching and Learning, 2025)
In the era of globalization and rapid technological development, increasing team productivity has become one of the main challenges for organizations. This research focuses on developing successful delegation as a strategy to increase team productivity. Using qualitative research methods, this study aims to identify keys that can increase delegation effectiveness and, in turn, improve team productivity. Through in-depth interviews with managers and team members from various industries, data was collected to explore their experiences and perspectives regarding delegation practices. Data analysis was carried out using a thematic approach, which resulted in several main themes: the importance of clear communication, selecting appropriate tasks, developing trust within the team, and providing constructive feedback. The research results show that effective communication and a deep understanding of team members' strengths and weaknesses are crucial factors in a successful delegation process. Additionally, building trust among team members allows for better decision making and increases commitment to delegated tasks. This research concludes that a good delegation strategy not only improves operational efficiency but also encourages team members' professional growth. By implementing the identified keys, organizations can create a more collaborative and productive work environment. These findings are expected to contribute to managerial practices and team development in various industrial sectors.